Peran Pewirausaha Wanita Dalam Meningkatkan Taraf Hidup Keluarga - Yovita Dyah Permatasari (INAIFAS Press, 2019)
The role of women experiences was developed, both in the family and in the order of life in the community and the state. The role of women in the family is no longer domestic but has evolved towards a multi-role that is public and economic. Women entrepreneurs have a role as supporters of the family economy and generate foreign exchange for the country. Home industry border in Sumberagung Village, Sumberbaru District, Jember Regency is managed by women. Based on this, this paper will reveal women entrepreneurs and their roles in the family, especially with regard to: entrepreneurial knowledge, efforts to increase business knowledge and skills, marketing results, the role of women in the family economy and ownership of family living facilities